EVALUATING THE EFFICACY OF NOVEL MOLECULES AGAINST SOYBEAN DEFOLIATORS - U. PATIL, MEENA; A. V. KULKARNI; GAVKARE, OMKAR (The Bioscan, 2014)
The field experiment was conducted at Aurangabad, Maharashtra, during 2009-10 and 2010-11 to study on the evaluation of novel insecticides for the management of Spodoptera litura (Fabrius) and Chrysodeixis acuta (Walkker) infesting soybean. Insecticides used in experiment Chlorantraniliprole 18.5%SC@ 30 g.ai/ha, Methomyl 40 % SP @ 300g.ai/ha , Spinosad 45% SC @ 75 g.ai/ha , Indoxacarb 15.8% EC @ 30 g.ai/ha, Thiodicarb 75 % WP @7 50 g.ai/ha, Trizophous 40% E.C @ 25 g.ai/ha and Profenofos 50 % EC @500 g.ai/ha . In both years there were significant difference detected across the treatment when these seven foliar insecticides used for the control of soybean defoliators. Among these insecticides, chlorantraniliprole (30 g.ai/ha), Methomyl (300g.ai/ha) and Spinosad (75 g.ai/ha) were found effective and statistically at par with each other in protecting the soybean crop from the infestation of both lepidopteran pests. Chlorantraniliprole provide consistent protection from defoliation to soybean crop from Spodoptera litura and Chrysodeixis acuta with highest cost benefit ratio among the tested insecticides.